Complement factor I from flatfish half-smooth tongue (Cynoglossus semilaevis) exhibited anti-microbial activities. Issue 1 (November 2015) - Xiang, Jinsong; Li, Xihong; Chen, Yadong; Lu, Yang; Yu, Mengjun; Chen, Xuejie; Zhang, Wenting; Zeng, Yan; Sun, Luming; Chen, Songlin; Sha, Zhenxia
Abstract: Complement factor I (Cfi) is a soluble serine protease which plays a crucial role in the modulation of complement cascades. In the presence of substrate modulating cofactors (such as complement factor H, C4bp, CR1, etc), Cfi cleaves and inactivates C3b and C4b, thereby controlling the complement-mediated processes. In this study, we sequenced and characterized Cfi gene from Cynoglossus Semilaevis (designated as CsCfi ) for the first time. The full-length cDNA of CsCfi was 2230 bp in length, including a 98 bp 5′-untranslated region (UTR), a 164 bp 3′-UTR and a 1968 bp open reading frame (ORF). It encoded a polypeptide of 656 amino acids, with a molecular mass of 72.28 kDa and an isoelectric point of 7.71. A signal peptide was defined at N-terminus, resulting in a 626-residue mature protein. Multiple sequence alignment revealed that Cfi proteins were well conserved with the typical modular architecture and identical active sites throughout the vertebrates, which suggested the conserved function of Cfi. Phylogenetic analysis indicated that CsCfi and the homologous Cfi sequences from teleosts clustered into a clade, separating from another clade from the cartilaginous fish and other vertebrates. Tissue expression profile analysis by quantitative real-time PCR (qRT-PCR) showed that CsCfi mRNA constitutively expressed in all tested tissues, with the predominant expression in liver and the lowest in stomach. Temporal expression levels of CsCfi after challenging with Vibrio anguillarum showed different expression patterns in intestine, spleen, skin, blood, head kidney and liver. The recombinant CsCfi (rCsCfi) protein showed broad-spectrum antimicrobial activities against the Gram-positive bacteria Staphylococcus aureus and the Gram-negative bacteria Escherichia coli, Pseudomonas aeruginosa and Shewanella putrefaciens . The research revealed that CsCfi plays an important role in C. Semilaevis immunity. Highlights: cDNA of CsCfi was first cloned and characterized in the flatfish. Deduced CsCfi protein had conserved structures with those of other species. Recombinant CsCfi protein displayed broad-spectrum antibacterial activities. CsCfi transcript was predominantly expressed in liver.